Effect of hot-dip galvanization on HC260LA steel scaffolding platform load capacity - Jastrzębski, Maciej; Misztela, Andrzej; Gołoś, Krzysztof (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2019)
The goal of the present paper is to examine the influence of hot-dip galvanisation process on mechanical properties of HC260LA steel (yield stress, ultimate stress and elongation) and scaffolding platforms load capacity. The galvanized welded scaffolding platforms manufactured from sheet thickness 1.25 mm were used in the tests. The experiments have shown the increase in load capacity of galvanised scaffolding platforms by 4.76 compared to the non-galvanised ones. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)